Korelasi Pengetahuan Tentang Covid-19 Dengan Self-Management Pasien Penyakit Kardiovaskular - Muliantino, Mulyanti Roberto; Ananda, Yuanita; Sarfika, Rika (Universitas Fort De Kock Bukittinggi, 2024)
Background: Self-management was essential part of health care in maintenance health status of patients with cardiovascular disease actually in the pandemic era. As the vulnerable population in the COVID-19 pandemic, they need an adequate knowledge of COVID-19 to prevent the infection. Knowledge of COVID-19 in line with the implementation of self-management in maintenance their health status.This study aimed to examine the correlation of knowledge of COVID-19 and self-management in patients with cardiovascular disease as vulnerable population in the pandemic era. Methods: This was cross-sectional study of 374 of patients with cardiovascular disease from Cardiovascular Centre in West Sumatera. We collected the knowledge of COVID-19 and self management using the Covid Related Cardiovascular Knowledge Questionnaire and the Cardiovascular Self Management related COVID-19 Questionnaire. Data were analysis with Spearman’s Rank Correlation. Results: The results showed that mean of knowledge of COVID-19 in patients with cardiovascular disease was 41,28 (SD=3,524) and mean of total self-management in cardiovascular patients was 77.7 (SD = 9.96). The further analyses showed that there was a significant correlation between knowledge of COVID-19 and self-management in cardiovascular patients (r = 0,215; p < 0,001). Conclusion: The degree of knowledge of COVID-19 was related to self-management in patients with cardiovascular disease. Patients with higher knowledge of COVID-19 have better implementation of self management in continuation care. Adequate education programme of COVID-19 infection and prevention was essential in patients with cardiovascular disease as vulnerable population to maintain their health status